Risk Factors and Early Symptoms Related to Respiratory Disease in Pedicab Drivers in Surabaya (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
Various factors which cause respiratory diseases such as smoking, air pollution, and disease history are found in pedicab. The purpose of this study was to understand the risk factors and early symptoms that related to respiratory disease in pedicab drivers. This study used observational cross-sectional design with purposive sampling. Variables that were recorded in this study were lung function risk factors and early symptoms of respiratory disorders. The number of samples was 148 respondents (135 with respiratory disorder and 13 without respiratory disorder). The results of this study found the most common risk factor was air pollution exposure. In 145 respondents (97.97%), the average lung function was 52.56%. The most frequent early symptom was dyspnea with percentage of 7.43% and average lung function value of 26.20%. Air pollution was the most common risk factor and dyspnea was the most common early symptom in pedicab drivers with respiratory disorders in Surabaya.